2018
DOI: 10.3892/ol.2018.9550
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in the survival time of patients with hepatocellular carcinoma and intrahepatic cholangiocarcinoma between Chinese patients and patients of other racial groups: A population‑based study from 2004 to 2013

Abstract: The aim of the present study was to investigate the racial disparities in the presentation, treatment and survival time of patients with hepatocellular carcinoma (HCC) or intrahepatic cholangiocarcinoma (ICC) between Chinese and other racial groups from the Surveillance, Epidemiology, and End Results (SEER) database between January 1st 2004, and December 31st 2013. Key covariates, including clinical presentation, treatment and survival time, were recorded and compared, demonstrating the racial differences. Kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Furthermore, this is also the first study to examine the survival of patients with HCC in mainland China. The median survival time was 31.0 months, which was similar to that of the Chinese patients in the U.S. (34.0 months) (42). The 1-, 3-, 5-, 10-year overall survival rates in this study were 60.6, 47.3, and 40.3%, respectively, which were slightly lower than in Taiwan, China (71.68, 57.14, and 47.82%) (40).…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, this is also the first study to examine the survival of patients with HCC in mainland China. The median survival time was 31.0 months, which was similar to that of the Chinese patients in the U.S. (34.0 months) (42). The 1-, 3-, 5-, 10-year overall survival rates in this study were 60.6, 47.3, and 40.3%, respectively, which were slightly lower than in Taiwan, China (71.68, 57.14, and 47.82%) (40).…”
Section: Discussionsupporting
confidence: 74%
“…high unemployment, high poverty, and low education areas) compared to the general population . Race/ethnicity was a significant independent prognostic factor in the HCC . The synergistic effect of contributing factors, including demographic, socioeconomic, biological, and treatment differences, will significantly enhance the racial disparity observed in survival time of HCC patients .…”
Section: Disparities In Socioeconomic Status and Health Care Accessmentioning
confidence: 98%
“…Race/ethnicity was a significant independent prognostic factor in the HCC . The synergistic effect of contributing factors, including demographic, socioeconomic, biological, and treatment differences, will significantly enhance the racial disparity observed in survival time of HCC patients . Socioeconomic disparities in the survival of patients with HCC continue to exist, and these differences could result from inequities in access to care and in response to therapy .…”
Section: Disparities In Socioeconomic Status and Health Care Accessmentioning
confidence: 99%
“…Several factors may play a role, including genetic factors. Previous studies have reported that Asian patient have better survival for iCCA and hepatocellular carcinoma [ 25 ]. Several genes have predictive value for CCA.…”
Section: Discussionmentioning
confidence: 99%